1973
DOI: 10.1073/pnas.70.5.1326
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of DNA in Chromatin to DNA Polymerase and RNA Polymerase

Abstract: The accessibility of DNA in chromatin to both exogenous DNA polymerase and RNA polymerase is slight when compared to isolated DNA. DNA in extracted chromatin is somewhat more accessible to these enzymes than is DNA in the chromatin of isolated nuclei; and the DNA template of chromatin is more accessible to DNA polymerase than to RNA polymerase. In these experiments we have given much attention to the technique of scintillation counting, since artifacts arising in this procedure can lead to erroneous conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…Other evidence for this viewpoint was provided by Stollar (18), who found that in native nucleoprotein (extracted chromatin) 1-5% of the DNA was available to react with antibody to DNA compared to about 20% of the DNA in dissociated-reassociated nucleo-protein. This finding is consistent with our observations that DNA in chromatin in the nucleus is only slightly accessible to deoxyribonuclease (2) and exogenous DNA arid RNA polymerases (13).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Other evidence for this viewpoint was provided by Stollar (18), who found that in native nucleoprotein (extracted chromatin) 1-5% of the DNA was available to react with antibody to DNA compared to about 20% of the DNA in dissociated-reassociated nucleo-protein. This finding is consistent with our observations that DNA in chromatin in the nucleus is only slightly accessible to deoxyribonuclease (2) and exogenous DNA arid RNA polymerases (13).…”
Section: Resultssupporting
confidence: 83%
“…Incubations and assays with E. coli DNA polymerase at pH 7.4 and RNA polymerase at pH 7.9 have been described (13). Evidence that the nuclear membrane does not affect accessibility to these enzymes has also been l)resented (1, 13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were either removed by a brief trypsin treatment or else scraped off in isolation buffer with a rubber policeman. In either case, the cells were washed once in 4 ml of isolation buffer (5 X 106 cells per ml) at 40 and then pelleted by centrifugation at 800 X g for 5 min at 4°. The pellet was then resuspended in isolation buffer at approximately 2 X 107 cells per ml.…”
Section: Methodsmentioning
confidence: 99%
“…Recently it has been shown that a short chain of RNA is associated with the nascent DNA, and it has been suggested that this RNA must be synthesized before the DNA can be replicated (3). Silverman and Mirsky (4) have shown that exogenous DNA polymerase and RNA polymerase both have much less access to the DNA in isolated nuclei or chromatin than in isolated DNA.…”
mentioning
confidence: 99%